(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, ports are in need to maximize their incomes, and this based on the fierce competition. For this reason, all ports stakeholders should be involved to contribute in the design and the development of a policy of scheduling and priority.This project owned by the Vessel Call Service Planning Service in the port of Tanger Med as the "Tanger Med Port Authority", and it output was to report the summarized the work done and the methods behind it.The main goal is to develop a simulator model that includes all kind of operations and the operational process by choosing the appropriate KPIs that are fully reflecting the congestion transferred by port vesselsFirst, it aims to define the operating assumptions and the fundamental concepts on which our simulation model will be based and to present the data that were used for the implementation of the simulation as well as the origin of these data.Secondly, it aims to validate and calibrate the model by presenting some improvements that could be made to the simulator in order to make it more precise and more representative and to ensure automation of the processing of inputs and outputs. While towards the end we conclude with the presentation of congestion situations, the results obtained and their use in decision making.AIS data is another factor has been added to help in getting best results, this helped in vessels planification in/out predictive process while automating the use of our simulator with the AIS Data receipt from SatelliteThis part of project is in to give the smart aspect to our simulator results by using smart technology.